Stages of pedagogical and psychological rehabilitation of children with cochlear implants with hearing impairments - PhD. Raximova Xurshidaxon Sadikovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article covers the methods of providing psychological and pedagogical assistance to children with hearing impairments and the problems of proper education and upbringing of children with hearing impairments as a result of the joint activities of family and specialists in the upbringing of weak hearing and deaf children, their formation as individuals, raising their position in society.